Exposure to online hate material and social trust among Finnish youth. Issue 3 (3rd August 2015) - Näsi, Matti; Räsänen, Pekka; Hawdon, James; Holkeri, Emma; Oksanen, Atte
Abstract : Purpose: – Trust is one of the key elements in social interaction; however, few studies have analyzed how the proliferation of new information and communication technologies influences trust. The authors examine how exposure to hate material in the internet correlates with Finnish youths' particularized and generalized trust toward people who have varying significance in different contexts of life. Hence, the purpose of this paper is to provide new information about current online culture and its potentially negative characteristics. Design/methodology/approach: – Using data collected in the spring of 2013 among Finnish Facebook users ( n =723) ages 15-18, the authors measure the participants' trust in their family, close friends, other acquaintances, work or school colleagues, neighbors, people in general, as well as people only met online. Findings: – Witnessing negative images and writings reduces both particularized and generalized trust. The negative effect is greater for particularized trust than generalized trust. Therefore, exposure to hate material seems to have a more negative effect on the relationships with acquaintances than in a more general context. Research limitations/implications: – The study relies on a sample of registered social media users from one country. In future research, cross-national comparisons are encouraged. Originality/value: – The findings show that trust plays a significant role in online setting. Witnessing hateful online material is common among young people. This is likely to have an impact on perceived social trust. Hateful communication may then impact significantly on current online culture, which has a growing importance for studying, working life, and many leisure activities.